Digital Transformation in Madrasah Assessment: An Analysis of Android-Based End-of-Year Assessment Implementation - Jufri, Jufri; Rahim, Abdul; Alan, Alan; Maulani, Sindy (Sekolah Tinggi Agama Islam Sumatera Medan, 2025)
Digital transformation in education, particularly in madrasahs, poses a major challenge in facing the Fourth Industrial Revolution and the development of information technology. At MTsN 1 Buton, the implementation of Android-based End-of-Year Assessment was chosen as a step to respond to these changes. This study uses a qualitative case study approach involving the madrasah principal, teachers, and students. The implementation process of the final assessment was carried out in three stages: planning, development, and implementation. The planning stage involved collaboration between madrasah leaders, teachers, and the information technology team to select the platform and map the devices. The exam application was developed with features such as random questions, time limits, and automatic saving. The exams were conducted in stages to avoid network disruptions. Challenges encountered included device limitations, internet access issues, low digital literacy, and potential cheating. Supporting factors included leadership support, teacher commitment, student enthusiasm, and the presence of a competent information technology team. This study demonstrates that synergy between commitment, digital literacy, and adaptive management is crucial. The implications of these findings contribute to more effective and inclusive digital assessment policies in madrasahs, emphasizing the importance of technology investment and risk mitigation strategies.